1984
DOI: 10.1007/bf00543495
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of radioreceptor assay and radioimmunoassay for atropine: Pharmacokinetic application

Abstract: A membrane suspension prepared from rat brain was able to bind the potent muscarinic antagonist quinuclidinyl benzilate (QNB). The KD for binding was 0.48 nM and Bmax was 1.42 pmol/mg protein. Atropine competitively inhibited the binding of tritiated QNB to muscarinic receptors. This new radioreceptor assay (RRA) for atropine has been compared with a radioimmunoassay (RIA) for atropine. The RRA measures only the active component of atropine, 1-hyoscyamine and in this respect it differs from the RIA. As little … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 13 publications
2
23
0
Order By: Relevance
“…This finding was consistent with the studies that used atropine sulphate to induce vagal blockade [31,39]. Atropine sulphate crosses the blood barrier [10,11], blocking central muscarinic cholinergic receptors, which results in the removal of its central inhibitory influence on muscle sympathetic nerve activity [13,40]. However, the LF power of blood pressure variability was not related to the muscle sympathetic nerve activity [41], but the LF pulse interval variability and the LF power of the blood pressure variability were correlated [31,42].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This finding was consistent with the studies that used atropine sulphate to induce vagal blockade [31,39]. Atropine sulphate crosses the blood barrier [10,11], blocking central muscarinic cholinergic receptors, which results in the removal of its central inhibitory influence on muscle sympathetic nerve activity [13,40]. However, the LF power of blood pressure variability was not related to the muscle sympathetic nerve activity [41], but the LF pulse interval variability and the LF power of the blood pressure variability were correlated [31,42].…”
Section: Discussionsupporting
confidence: 88%
“…Following one hour of recovery in the supine position, the protocol was repeated after an administration of repeated small (0.2 mg) intravenous doses of glycopyrrolate until there was no further increase in HR (group average dose of 12.0 ± 1.0 µg/kg body weight; range of 8.6-16.9 µg/kg body weight). We used glycopyrrolate to affect cholinergic blockade instead of the more commonly used atropine sulphate because atropine sulphate crosses the blood-brain barrier and influences central muscarinic receptors [10,11], confounding the interpretation of responses exhibited in the systemic circulation [12,13].…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to Prop, the volumes of distribution at steady-state for Hyosc enantiomers were similar (V ss /f = 7.82 ± 2.66 L/kg vs. 7.73 ± 1.39 L/kg). These trends are consistent with the pharmacokinetic study reported by Aaltonen and co-workers, where either S-Hyosc or Hyosc were measured with radioreceptor assay or radioimmunoassay, respectively [42]. They reported stereospecific differences in pharmacokinetics of R-and SHyosc with more than three times smaller AUC for S-Hyosc in comparison to Hyosc.…”
Section: Assay Applicationsupporting
confidence: 89%
“…The serum levels of anticholinergic activity in the same samples were determined by a radioreceptor assay according to Aaltonen et al (1983). The incubation medium (300 ,ul) Aaltonen & Scheinin (1982).…”
Section: Methodsmentioning
confidence: 99%